Relationship between Social Capital and Mental Health among the Older Adults in Aceh, Indonesia - Sufyan Anwar1,2, Stefanus Supriyanto3 , Wasis Budiarto3 , Rachmat Hargono3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: It is recognized that social capital plays an important role in health, including mental health. However, there are only a few studies that explain the role of social capital in the mental health of older adults in Aceh, Indonesia. This study aims to assess the relationship between social capital and the mental health of older adults. Method: This study used cross-sectional design by involving 483 respondents aged 60 or above, which are retrieved by using multistage random sampling in Aceh Barat District. Data collection was conducted for four months in 2019. SPSS Version 21 was used to analyze the data through a logistic regression test. Result: The result shows that the average age of respondents is 69.76 years and female respondents are 68.9%. The result of logistic regression analysis to conclude the relationship between social capital and mental health resulted in confidence level (p=0.044), social cohesion (p=0.021), social network (p=0.001), and social participation (p=0.119). Conclusion: The result indicates that social capital includes a social network, social cohesion, and trust are significantly relevant to the mental health of older adults.